A case report of tubulointerstitial nephritis and uveitis syndrome in children with an unfavorable outcome - Sang I Kong; Mun Hyang Park; Eun Jung Cheon (Korean Society of Pediatric Nephrology, 2023)
Tubulointerstitial nephritis and uveitis (TINU) syndrome is defined as the occurrence of tubulointerstitial nephritis and uveitis in the absence of other systemic diseases. Three pediatric cases have been reported in the Republic of Korea, and we now report a fourth case. A 15-year-old girl presented to the ophthalmology department with a 1-week history of bilateral ocular discomfort that worsened on the day of presentation with redness and pain in both eyes. She was diagnosed with bilateral uveitis, and her baseline examination revealed moderate renal dysfunction and mild proteinuria. A renal biopsy was performed and confirmed the diagnosis of TINU syndrome. She was started on steroid eye drops and a 12-week course of oral steroids at a dose of 40 mg/m2/day, which completely resolved the proteinuria and mild renal function to an estimated glomerular filtration rate of 60 mL/min/1.73 m2. However, the uveitis did not improve, and despite the addition of oral methotrexate as a second-line treatment, the uveitis remains unresponsive to treatment over 21 months. Further evaluation and treatment are ongoing, and active therapeutic intervention is suggested even at a pediatric age, considering the lack of improvement in renal function and uveitis to date.